Managerial competencies for multinational businesses - López- Fernández, Macarena; Romero-Fernández, Pedro M. (Hershey, PA, 2018)
"There is a growing interaction between companies and countries, illustrated by a constant flow of trade, capital, and work. With the rapid emergence of other countries with sufficient potential to join the globalization process, it is necessary to provide techniques for managerial planning, organization, and control in an international context. Managerial Competencies for Multinational Businesses is a collection of innovative research on the methods of leadership styles and skills required for managers to be successful in an international company. Highlighting a range of topics, including human resource management, industrial relations, and international careers, this book is ideally designed for senior managers, business professionals, team leaders, and human resource managers seeking current research on the key aspects of managing a company in a developing globalized market."